Effect of housing system on behavioural activity of lactating buffaloes - F. Grasso; A. Bilancione; F. Napolitano; A. Bordi; G. De Rosa (Italian Journal of Animal Science, 2010)
In order to verify the effect of a pool on behaviour and milk yield, eighty-eight lactating buffalo cows equally allocated to two treatments were used. Group WP was provided with a concrete pool of 208 m2, 36 m2/ head + 10 m2 of outdoor and indoor space allowance, respectively, whereas group NP only received 10 m2. Less animals from group WP were observed idling (P<0.05) compared to buffaloes from group NP, whereas subjects provided with a pool were more often involved in investigative activities (locomotion and exploration) than cows without access to it (P< 0.01). A higher number of social interactions (sniffing and nuzzling) and allogrooming were observed in group WP than in group NP (P< 0.01 and P< 0.05, respectively). The WP buffalo cows exhibited a higher yield of milk than NP subject (P< 0.05), whereas no differences between the two groups were observed for protein and fat contents. The provision of a pool can have beneficial effects on behaviour and milk production of buffaloes.